Mitochondrial disruption occurs downstream from β-adrenergic overactivation by isoproterenol in differentiated, but not undifferentiated H9c2 cardiomyoblasts: Differential activation of stress and survival pathways - Branco, Ana F. (2013)
β-Adrenergic receptor stimulation plays an important role in cardiomyocyte stress responses, which may result in apoptosis and cardiovascular degeneration. We previously demonstrated that toxicity of the β-adrenergic agonist isoproterenol on H9c2 cardiomyoblasts depends on the stage of cell differentiation. We now investigate β-adrenergic receptor downstream signaling pathways and stress responses that explain the impact of muscle cell differentiation on hyper-β-adrenergic stimulation-induced cytotoxicity. When incubated with isoproterenol, differentiated H9c2 muscle cells have increased cytosolic calcium, cyclic-adenosine monophosphate content and oxidative stress, as well as mitochondrial depolarization, increased superoxide anion, loss of subunits from the mitochondrial respiratory chain, decreased Bcl-xL content, increased p53 and phosphorylated-p66Shc as well as activated caspase-3. Undifferentiated H9c2 cells incubated with isoproterenol showed increased Bcl-xL protein and increased superoxide dismutase 2 which may act as protective mechanisms. We conclude that the differentiation of H9c2 is associated with differential regulation of stress responses, which impact the toxicity of several agents, namely those acting through β-adrenergic receptors and resulting in mitochondrial disruption in differentiated cells only.